Fiber bundle-based chemiluminescence array detection. Issue 22 (24th May 2021) - Chen, Gen; He, Tan; Sun, Song; Bao, Jun; Cui, Hua; Gao, Chen
Abstract : The development of multiplex analysis system for chemiluminescence on a single chip is highly desired. Abstract : Chemiluminescence (CL) is a dominant technology in clinical diagnosis. In order to meet the increasing demand for the sensitive and simultaneous detection of chemiluminescence from multiple samples, the development of multiplex analysis on a single chip is highly desired. However, most chemiluminescence detection systems for multiple samples are still simple lens-based optical imaging systems, and a compromise must always be made between a large aperture (required by the weak chemiluminescence) and a large field of view (required by the size of the sample array). In this paper, we report a fiber bundle-based chemiluminescence detection system for the simultaneous and efficient detection of multiple chemiluminescent samples. In this system, one side of the fiber bundle is directly coupled to the optically active surface of a charge-coupled device (CCD), while the other end is divided into many sub-bundles that are aligned above the samples in a chemiluminescence array to collect their chemiluminescence. Taking advantage of the large numerical aperture and high transmittance of optical fibers, this system shows about a 50 times increase in chemiluminescence collection efficiency over the lens-based imaging system. Moreover, it shows no vignetting effect that is inevitable in a lens-based imaging system with a large field of view. This work provides a promising method for multiple sample chemiluminescence detection, and should find application in bioassays.